2023
DOI: 10.1002/anie.202310115
|View full text |Cite
|
Sign up to set email alerts
|

Precise Recognition in Water by an Endo‐Functionalized Cavity: Tuning the Complementarity of Binding Sites

Yan‐Fang Wang,
Song‐Meng Wang,
Xiaobin Zhang
et al.

Abstract: Precise binding towards structurally similar substrates is a common feature of biomolecular recognition. However, achieving such selectivity—especially in distinguishing subtle differences in substrates—with synthetic hosts can be quite challenging. Herein, we report a novel design strategy involving the combination of different rigid skeletons to adjust the distance between recognition sites within the cavity, which allows for the highly selective recognition of hydrogen‐bonding complementary substrates, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…These values are consistent with the previous calculation, and indicate a slight NÀ H distance change of 1 Å in the cavity. In addition, the crystal structures of 3 a in n-hexane/CH 2 Cl 2 , 3 b in acetone/ CH 2 Cl 2 , and 4 a in acetone/CH 2 Cl 2 were also obtained [22] (Figures S13-S15, Table S1), which further confirmed the authenticity of the hosts' structure. These crystal structures reveal that solvent molecules can reside in the cavities of these hosts by forming weak non-covalent interactions, such as hydrogen bonding.…”
Section: (Figures S4-s5supporting
confidence: 57%
See 3 more Smart Citations
“…These values are consistent with the previous calculation, and indicate a slight NÀ H distance change of 1 Å in the cavity. In addition, the crystal structures of 3 a in n-hexane/CH 2 Cl 2 , 3 b in acetone/ CH 2 Cl 2 , and 4 a in acetone/CH 2 Cl 2 were also obtained [22] (Figures S13-S15, Table S1), which further confirmed the authenticity of the hosts' structure. These crystal structures reveal that solvent molecules can reside in the cavities of these hosts by forming weak non-covalent interactions, such as hydrogen bonding.…”
Section: (Figures S4-s5supporting
confidence: 57%
“…Subsequently, the distances between two NÀ H bonds within the cavities of these hosts were measured, and show the order 1 a � 1b < 3c � 4c < 2 (Figure 2d, Figure S10). The single crystal structures [22] of 3 a and 4 a further confirmed that regulating the structure of the rigid skeleton can effectively adjust the distance between binding sites. As shown in Figure 3 (Figures S11-S12, Table S1), the NÀ H bonds in both 3 a and 4 a are oriented inward towards the well-defined cavities.…”
Section: (Figures S4-s5mentioning
confidence: 71%
See 2 more Smart Citations
“…Jiang and co-workers have performed pioneering work to develop macrocyclic naphthotubes with diverse inside-cavity binding sites through utilizing different functional groups as linkers of their naphthotubes. 3a, 5 Macrocyclic arenes, which are macrocycles composed of hydroxy-or alkoxy-substituted aromatic rings linked by methylene groups, have undergone rapid development in supramolecular chemistry in recent years. 6 Calixarenes and pillararenes are classic macrocyclic arenes that have been widely studied in various areas, including molecular recognition, self-assembly, supramolecular materials, etc., 7 due to their unique aromatic structure and facile derivatization.…”
mentioning
confidence: 99%